Photovoltaic Panels Temperature Regulation Using Evaporative Cooling Principle: Detailed Theoretical and Real Operating Conditions Experimental Approaches - Zeyad A. Haidar; Jamel Orfi; Zakariya Kaneesamkandi (Energies, 2020)
Solar photovoltaic (PV) applications are gaining a great interest worldwide and dominating the renewable energy sector. However, the solar PV panels’ performance is reduced significantly with the increase in their operating temperature, resulting in a substantial loss of energy production and poor economic scenarios. This research contributes to overcoming the PV performance degradation due to the temperature rise. This work involves experimental and theoretical studies on cooling of PV panels using the evaporative cooling (EC) principle. A new EC design to cool the bottom surface of a PV panel was proposed, fabricated, tested, and modeled. A series of experimentation readings under real conditions showed the effectiveness of the method. A steady state heat and mass transfer model was implemented and compared with the experimental data. Fair agreement between the results of the modelling and experimental work was observed. It was found that the temperature of the PV panel can be decreased by 10 °C and the power improvement achieved was 5%. Moreover, the EC helps to stabilize the panels’ temperature fluctuation, which results in a better regulation of electrical power output and reduces the uncertainty associated with solar PV systems.